Review of Community based disaster Risk Management and Hazards Mapping in Afghanistan - Peroz, Sharifullah; Mashwani, Hayatullah (Journal of Natural Sciences – Kabul University, 2023)
Community-based Disaster Risk Management(CBDRM) is the process of disasters management that increases the coping capacity of community residents against disasters to reduce the level of vulnerability. The overall aim of this study is to build up community capacity in terms of disaster management in Afghanistan. This research is conducted based on review of books, international journals, and officially published reports as well as collecting data via social mapping at provincial levels. The result shows that the community-based disaster risk management (CBDRM) level is to very low. Therefore, based on this research it is suggested to responsible organizations to build and increase community-based disaster risk reduction committees at the community level.